Analisa Perhitungan Diameter Pipa Kapal Berdaya Mesin 4000 BHP - Pramono, Sri; Affiyanto, Deny (Universitas Ivet, 2024)
The pipeline system has an important role in the general service on board. Because without a pipeline system the pump as a means to move fluid from one place to another cannot flow or move the fluid. Pipeline systems in general include fuel pipes, lubricating oil pipes, fresh water pipes, sanitary water pipes, ballast water pipes, bilga pipes, fire pipes. Pipe installation systems include pipes, flanges, valves, separator attachments. The installation system is expected to produce an efficient pipe installation network both in terms of laying and safety in accordance with the classification regulations and from the installation guide specifications of the machining support system. In determining the diameter of fuel pipes, lubricating oil pipes, drinking water pipes, sanitary water pipes, ballast water pipes, bilga pipes, fire extinguisher pipes based on: type of fluid flowing in the pipe, volume of fluid to be moved, speed of fluid flow will be moved, also pay attention to the pressure due to friction.